Economic concepts and ideas of Al-Bukhārī: an analysis of the book of sales in Ṣaḥīḥ Al-Bukhārī - Ariffin, Muhammad Irwan; Tahir, Ibrahim Nuhu (2022)
This paper attempts to map the economic ideas of Al-Bukhārī that are reflected in the titles of the chapters in the Book of Sales in Ṣahīḥ Al-Bukhārī. The Book of Sales is used as the representative sample of hadiths related to muamalah in Saḥīḥ Al-Bukhārī. The economic ideas of Al-Bukhārī are derived using the methodology of interpreting the chapters’ titles and deduced from the general meaning of hadiths listed in the chapters. There are 25 chapters in the Book of Sales where the opinions of Al-Bukhārī are expressed directly. The economic ideas of these 25 chapters are then mapped to the classifications of hadiths into economic themes as analyzed in previous studies. Six major economic ideas were derived from these chapters, which are permissibility of credit transactions, honesty and truthfulness in business, market mechanism, importance of information and danger of uncertainty, controversial practices and prohibited sales, and land ownership and public finance.